Difference between X-ray-induced and 451 nm LD-induced photodarkening in DyAlGe-doped silica glasses. (1st April 2023) - Okazaki, T.; Kawai, K.; Otsuka, C.; Sekiya, E. H.; Kanbayashi, Y.; Mizusaki, M.; Saito, K.
Abstract: The difference between X-ray-induced photodarkening (X-PD) and 451 nm laser diode (LD) induced PD (LD-PD) was investigated in DyAlGe-doped silica glasses. The same defect species (Al-OHC, Dy 2+, GEC, and GLPC + ) are generated in X-PD and LD-PD, although the LD-PD defect population is 10 −3 of the X-PD defect population. There is a big difference in the defect population ratio of GEC and Al-OHC and its dependence on Ge concentration. The ratio in LD-PD is higher than that in X-PD. The GEC population of X-PD almost saturates when Ge > 2 wt%. On the other hand, GEC of LD-PD continues to increase even if Ge exceeds 2 wt%. Based on these facts, possible mechanisms of LD-PD and the role of Ge codoping were proposed.